Measuring the Impact of Financial Performance and Firm Age on Tax Avoidance - Irawati, Wiwit; Raphael, Alexander; Barli, Harry (Universitas Kristen Maranatha, 2025)
Purpose – This study aims to examine the influence of Financial Performance using the Return on Assets (ROA) and Debt to Equity Ratio (DER) proxies as well as Company Age on Tax Avoidance in Public Companies in Indonesia in the non-cyclical sector in 2019-2023. Design/Methodology/Approach – This study uses a quantitative approach, where the collected numbers are processed using the statistical tool STATA using the selected Fixed Effect /Model. The tests carried out were balanced panel data regression and data testing, namely autocorrelation test, multicollinearity and heteroscedasticity test. The research population amounted to 125 non-cyclical companies listed on the Indonesia Stock Exchange (IDX) in 2019-2023 with a selected sample using purposive sampling totaling 35 companies so that the total number of data processed was 175.Findings – The results of the study show that there is a partial significant influence of Financial Performance by proxy of Return on Asset and Debt to Equity Ratio and Company Age on Tax Avoidance. Research limitations/Implications – With new research data can be an input for policymakers related to decisions related to policies in the tax sector, especially for companies that have been operating for a long time and have a high level of profit and debt burden that will be able to trigger tax avoidance. Keywords: Company Size, Financial Performance, Tax Avoidance